Thermal Analysis of Certain Alkali Metal Malonates - Bassi, P.S.; Randhawa, B.S.; Kaur, Sandeep (Asian Journal of Chemistry, 2010)
The thermal analysis of alkali metal malonates (M═Li, Na, K, NH4) has been studied using TG—DTG—DTA, DSC and IR. M—O bond frequency in IR shows increasing trend with increase in electronegativity/polarizing power of the substituent cation. Kinetic parameters for various steps have been reported and high values for activation energy and frequency factor are attributed to the coupling of phase changes and the chemical steps. The stability order of decomposition in nitrogen atmosphere is Li > Na > K > NH4.